2004
DOI: 10.1038/ni1050
|View full text |Cite
|
Sign up to set email alerts
|

ST2 is an inhibitor of interleukin 1 receptor and Toll-like receptor 4 signaling and maintains endotoxin tolerance

Abstract: The Toll-interleukin 1 receptor (TIR) superfamily, defined by the presence of an intracellular TIR domain, initiates innate immunity through activation of the transcription factor NF-kappa B, leading to the production of proinflammatory cytokines. ST2 is a member of the TIR family that does not activate NF-kappa B and has been suggested as an important effector molecule of T helper type 2 (T(H)2) responses. We show here that the membrane-bound form of ST2 negatively regulated type I interleukin 1 receptor (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
418
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(443 citation statements)
references
References 37 publications
21
418
1
3
Order By: Relevance
“…33 Aside from its role in directing Th2-type responses, ST2L also has a well-characterized inhibitory effect on MyD88-dependent TLR activation. 17,49,50 Although TLR activation can promote Th2-type allergic inflammation, 51 targeting TLR9 with CpG has proved to be a highly effective therapeutic approach in experimental asthma. 52 The containment of Aspergillus in the allergic host requires TLR9 expression, 30 and exogenous CpG reverses fungal asthma when administered at a dose of 50 g for 2 weeks by intranasal, but not i.p., injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Aside from its role in directing Th2-type responses, ST2L also has a well-characterized inhibitory effect on MyD88-dependent TLR activation. 17,49,50 Although TLR activation can promote Th2-type allergic inflammation, 51 targeting TLR9 with CpG has proved to be a highly effective therapeutic approach in experimental asthma. 52 The containment of Aspergillus in the allergic host requires TLR9 expression, 30 and exogenous CpG reverses fungal asthma when administered at a dose of 50 g for 2 weeks by intranasal, but not i.p., injection.…”
Section: Discussionmentioning
confidence: 99%
“…55 Asthmatic DCs produced significant amounts of IL-12p70 after CpG activation, but it was evident from the present study that the ST2L had an inhibitory effect on CpGmediated generation of this cytokine. Because IL-33 protein was not detected in culture supernatants of DCs, the increased presence of ST2L alone on these cells might have been sufficient to sequester the adaptor protein MyD88 17 or inhibit I B␣ degradation, 56 thereby impairing TLR signaling. These findings are consistent with the observations of Espinassous et al, 57 who showed that the exogenous addition of IL-33 enhanced lipopolysaccharide activation in macrophages, findings that mirror those we obtained from cultured asthmatic DCs (H.R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have suggested that sST2 protein could be involved in the inflammatory response as well as in Th2 immune responses [43,44]. Some evidence suggests that sST2 could act as an anti-inflammatory mediator, through a mechanism that involves the inhibition of Toll-like receptor signaling by sequestration of MyD88 and Mal adapter proteins [45,46] or inhibition of I-κB degradation [47] resulting in down-regulation of NF-κB. In vitro and in vivo experiments have shown that sST2 protein or an ST2-fusion protein is able to attenuate the production of pro-inflammatory cytokines IL-1β, TNF-α, IL-6, and IL-12 [30,45,48].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that these two proteins function as receptor accessory proteins like AcPL. Intriguingly, a recent gene-targeting study suggested that T1/ST2 probably functions to inhibit IL-1R and TLR4 signaling (20). Although T1/ST2 cannot bind to IL-1, its TIR domain is capable of binding and probably sequestering common signaling molecules such as MyD88, preventing them from being used by IL-1R (20).…”
mentioning
confidence: 99%